2008
DOI: 10.2134/agronj2007.0195
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Seed Quality of Windmillgrass Ecotypes in South Texas

Abstract: Seeds A gronomy J our n al • Volu me 10 0 , I s sue 4 • 2 0 0 8 1205 ABSTRACT Hooded windmillgrass (Chloris cucullata Bisch.) and shortspike windmillgrass (C. subdolichostachya Muell.) are native grasses with potential for restoration of wildlife habitat. Th is study was conducted to characterize variability in windmillgrass seed quality as aff ected by temperature and precipitation. Seed-fi ll was superior in 2005 with 18% compared with 10 and 5% obtained in 2003 and 2004, respectively. Hooded ecotypes had hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
4
0
1
Order By: Relevance
“…It could be concluded with this that the persistence of the species is assured under unfavorable conditions as argued by Abdel Ghani et al (2002) for Hordeum spontaneum and H. vulgare. Similar results were obtained by Herrera et al (2008) in Chloris cucullata and C. subdolichostachys where the percentage of full and dormant seeds changed among years with different distributions of precipitation, but without altering viability.…”
Section: Reproductive Biomass Productionsupporting
confidence: 82%
“…It could be concluded with this that the persistence of the species is assured under unfavorable conditions as argued by Abdel Ghani et al (2002) for Hordeum spontaneum and H. vulgare. Similar results were obtained by Herrera et al (2008) in Chloris cucullata and C. subdolichostachys where the percentage of full and dormant seeds changed among years with different distributions of precipitation, but without altering viability.…”
Section: Reproductive Biomass Productionsupporting
confidence: 82%
“…Seedling emergence is determined by several factors, with water availability being the most important factor (Herrera et al, 2008). Water availability also affects the proportion of seeds with tegumentary dormancy and the proportion of nonviable seeds (Johnston et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we have to consider the biotypes used in this study did not originate at the same site, with the same environmental conditions. We know one of the factors affecting seed quality is the site of seed production (RAO et al 2017), in spite of, in some cases, no influence may also be observed (HERRERA et al 2007). However, almost all studies on weed resistance is carried out using biotypes from different places, because is not easy to obtain seeds of susceptible-and resistant-biotypes from the same site.…”
mentioning
confidence: 99%